Activated Prothrombin Complex Concentrates for the Reversal of Anticoagulant-Associated Coagulopathy - Awad, Nadia I. (MediMedia USA, Inc., 2013)
OBJECTIVE: Prothrombin complex concentrate (PCC) products are emerging as alternative strategies for reversing anticoagulant pharmacotherapy. Factor eight inhibitor bypassing activity (FEIBA, or anti-inhibitor coagulant complex) is an activated PCC (aPCC). Although FEIBA is approved by the FDA to control spontaneous bleeding episodes and to prevent bleeding with surgical interventions in hemophilia A and hemophilia B patients with inhibitors to factor VIII, recent data have suggested that the product may be used off-label as an anticoagulant-reversal agent. To evaluate the safety and efficacy of aPCC products in reversing anticoagulant pharmacotherapy, we searched online databases for English-language publications that discussed this topic. Data Sources: The EMBASE, MEDLINE, and International Pharmaceutical Abstracts databases were used. We evaluated all articles published in the English language identified from the data sources. We included studies conducted in human subjects and in in vitro and in vivo models in our review. RESULTS: Current published evidence suggests that the use of an aPCC, compared with fresh-frozen plasma, is associated with a significantly faster correction of supratherapeutic International Normalized Ratios (INRs) secondary to warfarin therapy. Conflicting evidence exists regarding the ability of aPCCs to reverse the prolonged bleeding times caused by the anticoagulant agents dabigatran etexilate (Pradaxa), rivaroxaban (Xarelto), apixaban (Eliquis), and fondaparinux (Arixtra). CONCLUSION: The theoretical risks of thrombosis associated with PCC products must be carefully considered before they are administered to patients who require coagulation therapy. The use of aPCCs to reverse the anticoagulant effects of warfarin, dabigatran, or rivaroxaban should be limited because of the lack of efficacy and safety data in humans. Moreover, the safety of aPCCs in off-label indications has not been adequately assessed.